P-143 The initial blastocyst size after warming is a strong predictor for clinical pregnancy in single vitrified blastocyst transfer. (30th June 2022) - Iversen, L; Gabrielsen, A; Veng Eskildsen, T; Ravn Hansen, S; Larsson, P; Mannaerts, B
Abstract: Study question: Which morphokinetic and morphological factors during embryo development before vitrification and after warming predict the chance of clinical pregnancy in single vitrified blastocyst transfer (SVBT)? Summary answer: Time to reach blastocyst stage, numeric Gardner score before vitrification and blastocyst size after warming correlate with clinical pregnancy but not post-warming expansion rate. What is known already: Several studies have evaluated pre-vitrification and post-warming characteristics of vitrified-warmed blastocysts to identify parameters that correlate with implantation. New pre-vitrification and post-warming morphokinetic parameters were identified by culturing embryos in time-lapse incubation systems before vitrification as well as after warming. Among others, the number of collapses before vitrification, the size after warming in combination with the post-warming expansion rate and the maximal expansion size was reported to have a significant correlation with implantation. To our knowledge these findings were so far not re-evaluated in another, independent study. Study design, size, duration: Analysis of 549 treatment/cryo cycles in 349 patients participating in a multicenter observational trial (IMBOS trial). Subjects received one controlled ovarian stimulation with follitropin delta (Rekovelle). Of 377 transfers, 195 were fresh day 5 single blastocyst transfers and 182 were SVBTs from blastocysts that were vitrified on day 5. Both fresh and vitrified-warmed embryos were cultured in a time-lapse system. Various morphokinetic parameters, including Gardner score, were assessed in the fresh cycle and after vitrification-warming. Participants/materials, setting, methods: Associations between clinical pregnancy (positive fetal heartbeat), morphokinetic parameters, blastocyst collapse, KIDScore D5, Gardner score before vitrification, blastocyst size after warming, re-expansion rate, and Gardner score before SVBT were investigated. Mixed logistic regression models were used with clinical pregnancy as dependent variable and different morphokinetic/morphological parameters as factors or covariates. Repeated transfers were accounted for by including subject as a random factor in models, with the log-odds for different subjects assumed to be normally distributed. Main results and the role of chance: A total of 182 SVBT resulted in 89 clinical pregnancies. For pre-vitrification parameters no clear association was found between the number of collapses (P = 0.6095) or the maximal collapse size (P = 0.9122) before vitrification and clinical pregnancy. Multifactorial analysis of Gardner score before vitrification only showed significant association with clinical pregnancy for trophectoderm grading (P = 0.0247), and not for expansion and hatching status and inner cell mass. There was no significant association for any of the Gardner score parameters when assessed immediately before SVBT. However, when the Gardner score was transformed into a total numerical score, significant associations with clinical pregnancy was noted both when assessed before vitrification (P = 0.0003) and before cryotransfer (P = 0.0005). From the analysis of time-lapse parameters, the time to reach blastocyst (tB-tPNf; P = 0.0288) and KIDScore D5 (P = 0.0035) were significantly associated with clinical pregnancy. Multifactorial analysis showed that size after warming was significantly associated with clinical pregnancy (P = 0.0257), but not rate of expansion (P = 0.4241) or maximal expansion size (P = 0.1789). The prognostic potential of trophectoderm grading and KIDScore D5 was previously reported. Further analysis showed a positive correlation between numeric Gardner score before vitrification and size after warming, but not between time to reach blastocyst (tB-tPNf) and size after warming. Limitations, reasons for caution: Blastocysts for SVBT were selected by each laboratorýs policy, which may constitute a selection bias. The proposed factors were derived by statistical analysis of a fixed dataset; offset thresholds for any of the parameters were not defined. Any potential clinical application must be tested and validated on an independent dataset. Wider implications of the findings: Selection for which vitrified blastocyst to warm first may benefit from using tB-tPNf rather than Gardner score. Size after warming does constitute an early post-warming parameter if a decision is needed to eventually warm another blastocyst. Trial registration number: NCT03697031